Analysing Malay Taboos from the Perspective of SPB4K Theory: (Pantang Larang dalam Kalangan Orang Melayu: Analisis dari Perspektif Teori SPB4K Pantang Larang dalam Kalangan Orang Melayu: Analisis dari Perspektif Teori SPB4K) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
Taboos are the prohibition of certain actions or speech in order to prevent something unwanted from happening. This article reviews whether the taboos of the Malay community are still relevant and should be followed from the perspective of the 4K Consolidated Thinking System Theory (SPB4K Theory) by looking at four different aspects: spiritual, incomparable, scientific and creative thinking. Spiritual thinking is closely connected to faith and the relationship between humans and the Creator as His servants (hablumminallah) and the relationshipas among human beings as God's vicegerents on earth (hablumminannas). Incomparable thinking studies the ways in which the Malays expressed taboos in order to educate and to inculcate good values. Scientific thought looks at the logic and the 'scientificness' of the thinking of the Malays of old regarding occurrences in the natural world such as rain and thunder, as well as the relationship of humans with the animal and plant world. Creative thinking looks at the creativity of the Malays in structuring the words and sentences in expressing their taboos to the extent that their descendants were afraid to breake these and would obey without question.Keywords: taboos, sanctity, incomparability, creativity, scientificness